If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(5x + -3) * 3.2 = 0 Reorder the terms: 8(-3 + 5x) * 3.2 = 0 Reorder the terms for easier multiplication: 8 * 3.2(-3 + 5x) = 0 Multiply 8 * 3.2 25.6(-3 + 5x) = 0 (-3 * 25.6 + 5x * 25.6) = 0 (-76.8 + 128x) = 0 Solving -76.8 + 128x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '76.8' to each side of the equation. -76.8 + 76.8 + 128x = 0 + 76.8 Combine like terms: -76.8 + 76.8 = 0.0 0.0 + 128x = 0 + 76.8 128x = 0 + 76.8 Combine like terms: 0 + 76.8 = 76.8 128x = 76.8 Divide each side by '128'. x = 0.6 Simplifying x = 0.6
| 5x-4x=2 | | -4k+3=11 | | -(4+12x)=32 | | 100=2(3.14)r | | 75=19 | | 6+8q=11x+7q | | x^2-40x+3200=0 | | -4+3=11 | | 4-3x=x-6 | | 6(8+x)-6x=8(x+5) | | 2x^2+12=-5x | | 0.30(x+10)+0.30x=12 | | 2(x+7)=5x-35 | | 5x-2=150 | | 100+20= | | -9i(7i-2)= | | 4x+6-2x+6= | | 12=-c+-1.5 | | -18+1p=-16 | | 25-40x=-.49x^2 | | 4x-4=127 | | f(n)=f(n-1)+18 | | 60p-30p=300 | | 3-(-6-9i)-(-7+2i)= | | 12x=6x-48 | | 3=-(-6-9i)-(-7+2i) | | 13=6x+4 | | 2+5y=4 | | -18=y-22 | | -x^2+29x-54=0 | | x+.15x+2.4=2(x-1.3) | | 1+5y=4 |